Cytotoxic Potensial and Molecular Docking of Essential Oil Piper Aduncum Flowers Against Cervical Cancer Cells - Rahmadani, Indah; Efdi, Mai; Suryati, Suryati (Universitas Pendidikan Mandalika, 2024)
Piper aduncum L., commonly known as spiked pepper, is a medicinal plant traditionally used to treat various diseases due to its diverse, active compounds. This article investigates the chemical composition, cytotoxic bioactivity in vitro and the silico of the essential oil (EO) from the flowers of Piper aduncum collected in Padang City, Indonesia. The EO was obtained by hydrodistillation using a Clevenger-type apparatus and characterized by gas chromatography-mass spectrometry (GC-MS). The in vitro cytotoxicity of the EO was assessed against cervical cancer (HeLa cancer cell line) using the MTT assay and further explored through molecular docking approaches. The main constituent of the essential oil from the flowers was dillapiol (31.68%). The LC50 and IC50 values were 31.3471 Âµg/mL and 65.83 Âµg/mL, respectively. Computational screening was performed to observe the interactions between active compounds and proteins AKT and ERK2 using molecular docking. AKT and ERK2 act as critical regulators in the PI3K/Akt and ERK/MEK signaling pathways and are potential drug targets for cancer therapy. The compounds used complied with ADMET analysis and toxicity profile. However, it is noteworthy that there have been no previous reports on the essential oil from Piper aduncum flowers from Padang City specifically targeting cervical cancer, which molecular docking studies have complemented. The results suggest that the essential oil from the flowers of Piper aduncum can be further studied as a potential lead in drug discovery for cervical cancer.